Design and development of precision localization measurement technique for low altitude UAV in paddy field monitoring application / Azhar Jaffar - Jaffar, Azhar (2019)
In Malaysia, rice has been adapted as the staple food for the nation. To raise the production from the paddy field, a modern technology must be adapted to the paddy plantation system. Over the years, in Europe especially, a new modern technology has been adapted in their agriculture system to help saving cost on plantation management. The jobs of fertilizing the crops, pesticide control, crops monitoring and harvesting are all done using automatic machinery system. By this way the farmers can maximize their production and expense less on farm management for a long period of time. All these positive development are done using the help of modern technology especially with the help of using the Global Positioning System (GPS). One of the greatest achievements by using the GPS is that the GPS has the ability to map the agriculture field so that a machine can move or works autonomously inside an assign boundaries of the field. One of the favourite modern technologies that have been used in an agricultural field is using the Unmanned Aerial Vehicle (UAV) or sometimes they called it as the drone. The UAV has the ability to do lot more of things from the air. The UAV has ability to fly at low altitude to spray the fertilizer and the pesticide and the most important task is that it can monitor the crops from the air. The movement of the UAV is usually manual controlled by the user and sometime there are also an autonomous UAV. Both of the control types have the help of the GPS for their positioning. Using the GPS has some setback on its own. The GPS is exposed to low signal problem, signal blockage and intentional or unintentional interference. On this work, other method of technique to replace the GPS is introduced.